2001
DOI: 10.1046/j.1365-3148.2001.00323.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a novel hepatitis B virus mutant: demonstration of mutation‐induced hepatitis B virus surface antigen group specific ‘a’ determinant conformation change and its application in diagnostic assays

Abstract: We report and characterize a novel mutant of the hepatitis B virus surface antigen (HBsAg). The mutant was isolated from a symptomatic patient who was found to be persistently positive for both HBsAg and anti-hepatitis B surface antibody (anti-HBs) and a long-lasting anti-HBc (core) IgM. Due to the unusual immune serological profile, polymerase chain reaction and sequencing were performed and revealed a genotype D mutant HBV (LBN). Aligned with known HBsAg sequences from GenBank, the LBN variant matched to con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(12 citation statements)
references
References 38 publications
0
11
0
1
Order By: Relevance
“…Similar HBsAg escape mutations in 2nd loop of the "a" determinant (S143L; S143 M) were observed in two virus strains causing fulminant hepatitis, but no such mutations were detected in asymptomatic and chronic hepatitis B patients (T. Michler et al, 2014). Luongo et al also reported a male patient with high seroprotective anti-HBs titer (>200 IU/l) and acute HB with three mutations (M125T, T127P and Q129H) in the virus strain (Kfoury et al, 2001). S gene mutants are the dominant HBV variants in immunized population with fulminant and acute HB (Hsu et al, 1997), because these mutations allow the virus to escape neutralization by antibodies and inefficient CTL-mediated control.…”
Section: S Gene Mutations In Patients With Hbv Vaccine Breakthrough Imentioning
confidence: 72%
See 1 more Smart Citation
“…Similar HBsAg escape mutations in 2nd loop of the "a" determinant (S143L; S143 M) were observed in two virus strains causing fulminant hepatitis, but no such mutations were detected in asymptomatic and chronic hepatitis B patients (T. Michler et al, 2014). Luongo et al also reported a male patient with high seroprotective anti-HBs titer (>200 IU/l) and acute HB with three mutations (M125T, T127P and Q129H) in the virus strain (Kfoury et al, 2001). S gene mutants are the dominant HBV variants in immunized population with fulminant and acute HB (Hsu et al, 1997), because these mutations allow the virus to escape neutralization by antibodies and inefficient CTL-mediated control.…”
Section: S Gene Mutations In Patients With Hbv Vaccine Breakthrough Imentioning
confidence: 72%
“…The mechanisms by which mutated virus causes HBV vaccine breakthrough infection include: 1) altered conformational structure and/or T-cell epitope structure allowing mutated virus to evade recognition and clearance by the immune system; 2) altered antigenicity of HBsAg through changes in hydrophobicity profile and putative glycosylation site, which consequently decrease or abolish affinity for anti-HBs, offering lower protection from vaccination (Luongo et al, 2015) and permitting infection with HBV isolates of different genotypes or subtypes in patients with a normal anti-HBs response (Wu et al, 2012); and 3) the accumulation of aa substitutions because of mutations in and around the "a" determinant region may change immunogenicity of HBsAg, producing less effective neutralizing anti-HBs response and enabling the mutated virus evade clearance and survive long terms (Kfoury et al, 2001). S gene mutations of HBV can occur in vaccinated population with fulminant, acute and chronic HB.…”
Section: S Gene Mutations In Patients With Hbv Vaccine Breakthrough Imentioning
confidence: 99%
“…These mutations especially include amino acid residues between the positions 19–28, 80–98, 110–120, 148–162 and 206–215 (Table ). It seems that, as an alternative, virus‐neutralizing activity may reside in antibodies related to distantly located amino acid residues in other parts of the protein rendering the viral particle less immunogenic in producing an effective neutralizing anti‐HBs response to clear the virus . Also, changes located outside the ‘a’ determinant region were reported from immunized infants born to HBV carrier mothers .…”
Section: Discussionmentioning
confidence: 99%
“…Mutations near the MHR can alter group-specific antigenicity even though the mutations are not within the MHR. [899495] Monoclonal antibody binding assays have also shown that residues 178-186 are exposed on the surface of the 20 nm particle. [96] This is the region which specifies the q sub-determinant.…”
Section: Escape Mutantsmentioning
confidence: 99%